Multicomponent Reactions in Water Medium Catalyzed by Zn-VCO3 Hydrotalcite: A Greener and Efficient Approach for the Synthesis of Multifunctionalized Benzenes - Pagadala, Ramakanth; Maddila, Suresh; Rana, Surjyakanta; B. Jonnalagadda, Sreekantha (Current Organic Synthesis, 2015)
A highly efficient method for synthesis of multifunctionalized benzenes by one-pot multicomponent condensation between malononitrile, substituted aldehyde and cycloheptanone catalyzed by Zn-VCO3 hydrotalcite is reported. With water as solvent, this green chemistry reaction entails mild conditions. It is atom-efficient, high-yielding and pertinent to an extensive variety of multicomponent reactions.
Keywords: water as a solvent